2020
DOI: 10.1186/s43094-020-00034-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of in vivo hypoglycemic effect of gliclazide by developing self-microemulsifying pellet dosage form

Abstract: Background The present research was aimed to develop a self-microemulsifying drug delivery system (SMEDDS) pellet to increase the dissolution rate and in vivo hypoglycemic effect of gliclazide. Gliclazide belongs to BCS class 2 and it exhibits dissolution rate-limited absorption. Thus, dissolution enhancement of gliclazide from its dosage form is a prime requirement to achieve a better therapeutic effect. The solubility of gliclazide was estimated in oils, surfactants, and co-surfactants. A most effective self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Furthermore, the optimized batch remained stable throughout the study period, suggesting that steric contributions from nonionic surfactants may promote stability in such systems. Our results are more promising than those reported by Patel et al, (17) . When the surface charge (Zeta potential) on oil globules is positively charged, emulsions become electrostatically attracted to the mucosal cell surface, resulting in increased drug bioavailability.…”
Section: Globule Size Zeta Potential Pi and Drug Contentsupporting
confidence: 73%
See 2 more Smart Citations
“…Furthermore, the optimized batch remained stable throughout the study period, suggesting that steric contributions from nonionic surfactants may promote stability in such systems. Our results are more promising than those reported by Patel et al, (17) . When the surface charge (Zeta potential) on oil globules is positively charged, emulsions become electrostatically attracted to the mucosal cell surface, resulting in increased drug bioavailability.…”
Section: Globule Size Zeta Potential Pi and Drug Contentsupporting
confidence: 73%
“…The study conducted by Patel et al also showed the highest solubility of Gliclazide in Capmul MCM C8 so used as oil for the development of SNEDDS. According to them, drug solubility is higher in medium-chain triglycerides (MCT) than in long-chain triglycerides (LCT) because MCT has a higher ester content per gram (17) . Our results are also consistent with already published research work.…”
Section: Saturation Solubility Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several formulation techniques have been adapted to improve the bioavailability and therapeutic effectiveness of gliclazide such as the preparation of solid dispersion [ 8 , 9 ], inclusion complex with β-cyclodextrin [ 10 ], nanocrystals [ 11 ], liquid–solid systems [ 12 ], solid lipid nanoparticles [ 13 ], and self-micro-emulsifying delivery system [ 14 ]. The previously mentioned approaches rely on increasing the solubility of gliclazide as a mechanism for bioavailability improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Theses formulations were developed as promising controlled delivery systems and loaded with Capmul ® MCM C8 for the potential enhancement of release and bioavailability of poorly water soluble drug. Patel et al have employed Capmul ® MCM C8 as a bioavailability enhancer in pellets designed for improved oral drug delivery of gliclazide [29]. The prepared formulations were loaded with 5% w/w of the antihypertensive agent, felodipine, as a model drug.…”
Section: Preparation Of Polymeric Films With Different Concentrationsmentioning
confidence: 99%